Review of the adaptive re-use of three colonial buildings in Dhaka, Bangladesh - Parvin, Mst Nargis (2016)
Adaptive reuse is a process of redevelopment and regeneration of historic building that can be reuse for new purposes which provides social, environmental and economic benefits. Bangladesh have experienced long colonial past (1757 to 1947). During colonial period developed many significant buildings with colonial style and character. These buildings had strong impact on society, culture and history. However, many of these colonial buildings are not conserving and well documented for future generation. As a result, several colonial buildings are gradually decaying and abandonedor used by illegal people. Very few buildings are conserving and reusing by the government however, most of these buildings are in critical condition. In this study, we evaluated the current situations of conservation and adaptive reuse of three British colonial buildings (Ahsan Monzil, Curzon Hall and Ruplal House) in Dhaka, Bangladesh. To get the optimum result, three British colonial buildings selected as sample and qualitative methods applied for study. Interview, documents study and observation are the three main techniques for qualitative method, which applied for data collection. In order to identify the challenges or problems between the conservation practice and current condition of adaptive reuse, have analyzed in existing framework or guide lines that provided by the government of Bangladesh and international conservation principles, which delivered by the UNESCO, ICOMOS, ICCOROM and international Charters. Based on the data collections have revealed multiple causes, which severely effects to the longevity and adaptive reuse of British colonial buildings, such as: lack of proper planning and guidelines by the government, insufficient fund, lack of expert technical people, ignorance of implementation, weaken of monitoring system and lack of people’s awareness. In such a deplorable condition, it is essential to reform the government framework, which followed by the international guidelines that provided by the international organizations and at the same time can full fill the all aspects and needs of Bangladesh’s colonial buildings adaptive reuse. If the government and related authorities initiates these types of actions, the people will get multiple benefits from adaptive reuse of colonial buildings, such as economic, social, cultural, job opportunity, recreational, environmental and logical connection with the past and future generation.